Analysis of Active Vs Passive Investment Behavior in Emerging Markets - Joshi, Girish Balkrishna; Dash, Ranjan (Zielona Góra: Faculty of Economics and Management Press)
Responses from 480 Indian respondents, 240 each investing in Mutual Funds and Exchange Traded Funds were studied to assess individual investors behavioral biases with the help of factors of herding, market, prospect, overconfidence and availability bias by using one way MANOVA approach. Results indicate that the Mutual Fund (active investment) investors show significantly higher behavioral biases as compared to Exchange Traded Fund (passive investment) investors in emerging markets.
Keywords: passive investments; active investments; exchange traded funds; mutual funds; MANOVA; investor behavior; financial literacy